Pengaruh Media Pembelajaran Audio Visual Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Sejarah Kebudayaan Islam Kelas VII Di MTS Al- Ahsan Kota Bogor - Muflihah, Siti Nur Inayah; Irfani, Fahmi; Hambari, Hambari (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research discusses the impact of audio-visual learning media on the learning outcomes of students in the Islamic cultural history subject in seventh grade at MTs. Al-Ahsan Kota Bogor. The objectives of this study are (1) to determine the learning outcomes of Islamic cultural history for the control group in MTs. Al-Ahsan Kota Bogor, (2) to assess the learning outcomes of Islamic cultural history for the experimental group in MTs. Al-Ahsan Kota Bogor, (3) to examine the influence of audio-visual learning media on the learning outcomes of students in the seventh-grade Islamic cultural history subject at MTs. Al-Ahsan Kota Bogor. The research employs a quantitative approach and a quasi-experimental method, with data collected through learning outcome tests administered to 59 students in the control group and 59 students in the experimental group. The results of the study indicate that: (1) the average post-test learning outcome score for the experimental group is 91.81, (2) the average post-test learning outcome score for the control group is 75.14, (3) the independent sample t-test yields a t-value of 11.767 with Sig. (2-tailed) 0.00 < 0.05, indicating a significant influence of audio-visual learning media on the learning outcomes of students in the Islamic cultural history subject in seventh grade at MTs. Al-Ahsan Kota Bogor. Therefore, the research accepts the alternative hypothesis (Ha) and rejects the null hypothesis (Ho). Consequently, if schools aim to enhance student learning outcomes, they should develop effective learning media to create a conducive and enjoyable learning environment.